Organizational behavior - Stephen P Robbins and others; ROBBINS (Stephen P); SANGHI (Seema); JUDGE (Timothy A) (New Delhi Pearson Prentice Hall, 2009)
Organizational Behavior, with its cutting-edge content, clear writing style, and compelling pedagogy, remains the global bestseller it has been for years. While maintaining its hallmark features, the thirteenth edition has been updated to reflect the most recent research and developments in the field of organizational behavior. With its tradition of making the text come alive with examples, case incidents, current research, and learning tools, Organizational Behavior is a necessary read for all managers, human resource workers, and anyone seeking to understand and improve their people skills. Special Features: * Improved S.A.L. Updated and expanded Self-Assessment Library (S.A.L.) with 25 additional tests * Updated Sections
Table of Contents I. INTRODUCTION 1. What Is Organizational Behavior? II. THE INDIVIDUAL 2. Foundations of Individual Behavior 3. Attitudes and Job Satisfaction 4. Personality and Values 5. Perception and Individual Decision Making 6. Motivation Concepts 7. Motivation: From Concepts to Applications 8. Emotions and Moods III. THE GROUP 9. Foundations of Group Behavior 10. Understanding Work Teams 11. Communication 12. Basic Approaches to Leadership 13. Contemporary Issues in Leadership 14. Power and Politics 15. Conflict and Negotiation IV. THE ORGANIZATION SYSTEM 16. Foundations of Organization Structure 17. Organizational Culture 18. Human Resource Policies and Practices V. ORGANIZATIONAL DYNAMICS 19. Organizational Change and Stress Management Appendix A: Research in Organizational Behavior Appendix B: Careers and Career Management